The differences between gross motor performance amongst children according to ethnic and age chronology - Jorrye Jakiwa; Pathmanathan K. Suppiah (2020)
Gross motor skills are important elements that are often associated with the activeness of children in sports and physical activity. The better motor performance level amongst children is reflected by the higher level of involvement in sports and physical activity. Therefore, the purpose of this study is to investigate the level of gross motor performance amongst children based on ethnic and chronological age. The subjects of the study consist of two different ethnic groups namely, Malays (n=38) and Indians (n=34), respectively. A total of 72 subjects aged between 8 and 9 years old (8.51 ± 50 years) volunteered for this study. The Test of Gross Motor Development (TGMD-2) is the instrument used in order to assess the gross motor performance amongst the children. Two gross motor components assessed were locomotor and object manipulation. The t-test analysis found that there was no significant difference on the level of motor performance between the ethnicities either in locomotor [t (70) = .31, p (.75)> .05] or object manipulation [t (70) = 1.65, p (.10)> .05]. Meanwhile, the results attained from the Gross Motor Quotient (GMQ) score demonstrated that all the participants regardless of their ethnicity, exhibited a lower level of gross motor performance compared to age equivalent standard score. In conclusion, ethnic differences do not affect the level of gross motor performance either in locomotor or object manipulation.